Anabolic Androgenic Steroids: Searching New Molecular Biomarkers - Sessa, Francesco; Salerno, Monica; Di Mizio, Giulio; Bertozzi, Giuseppe; Messina, Giovanni; Tomaiuolo, Benedetta; Pisanelli, Daniela; Maglietta, Francesca; Ricci, Pietrantonio; Pomara, Cristoforo (Frontiers in Pharmacology, 2018)
Even if anabolic androgenic steroid (AAS) abuse is clearly associated with a wide spectrum of collateral effects, adolescents and athletes frequently use a large group of synthetic derivatives of testosterone, both for aesthetic uses and for improving performance. Over the last few years, the development of MicroRNA (miRNA) technologies has become an essential part of research projects and their role as potential molecular biomarkers is being investigated by the scientific community. The circulating miRNAs detection as a diagnostic or prognostic tool for the diagnosis and treatment of several diseases is very useful, because with a minimal quantity of sample (peripheral blood), miRNAs are very sensitive. Even more, miRNAs remain stable both at room temperature and during freeze-thaw cycles.These characteristics highlight the important role of miRNAs in the near future as new tools for anti-doping. The article provides a systematic review and meta-analysis on the role of miRNAs as new potential molecular biomarkers of AAS use/abuse. Particularly, this paper analyzed the "miRNA signature" use as biomarkers for health disorders, focusing on the organ damages which are related to ASS use/abuse. Moreover, this review aims to provide a future prospect for less invasive or noninvasive procedures for the detection of circulating miRNA biomarkers as doping assumption signaling.